Grief and Mourning During the COVID-19 Pandemic: A Psychological and Pastoral Perspective - Trębski, Krzysztof (Rocznik Teologii Katolickiej, 2021)
This article considers the difficulties associated with grief, mourning, and healing during the COVID-19 pandemic. The current pandemic has affected the way individuals overcome grief, since the bereaved must grieve without the usual social, cultural, and religious supports. Due to the ban on visiting the sick in hospitals as well as gathering and mourning in funeral homes, many people are experiencing pathological grief. This article indicates the importance of pastorally accompanying people who are going through the complicated process of mourning,1 and it emphasizes that, through spiritual help and psychological accompaniment, this period can lead to healing that results in posttraumatic adaptation (resilience) and inner development.